Semiotic Analysis of Moral Messages in Otto’s Character From “A Man Called Otto (2022)” Movie - Nabila Zahra, Defita; Prastiwi, Yeny (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
Movies are one of those media communication that can convey messages. “A Man Called Otto” movie directed by Marc Forster is an illustration that reflects life lessons and moral messages. The study aims to explore how social signs are presented in movies through a semiotics approach with a focus on the development of Otto’s character. Through the theory of Roland Barthes, this analysis explains the connotation and denotation concept to understand how elements such as settings, character, dialogue, and symbols convey broader meanings. With descriptive qualitative analysis, authors describe data based on personal interpretation and understanding. Data is drawn from movie observations and using several references such as journal articles, books, and others to support statements. The findings show that there are seven moral messages in the main character of Otto, namely Empathy, Loyalty, Kind, Bravery, Honesty, Heroism, and Generous. This study contributes to offering knowledge of how signs and symbols used in the movies to communicate messages in social and cultural contexts.